Type II alveolar epithelial cell aryl hydrocarbon receptor protects against allergic airway inflammation through controlling cell autophagy - Wang, Ji; Zhao, Yilin; Zhang, Xin; Tu, Wei; Wan, Rongjun; Shen, Yingchun; Zhang, Yan; Trivedi, Ruchik; Gao, Peisong (Frontiers in Immunology, 2022)
Rationale: Aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor, has been considered as an important regulator for immune diseases. We have previously shown that AhR protects against allergic airway inflammation. The underlying mechanism, however, remains undetermined. Objectives: We sought to determine whether AhR specifically in Type II alveolar epithelial cells (AT2) modulates allergic airway inflammation and its underlying mechanisms. Methods: The role of AhR in AT2 cells in airway inflammation was investigated in a mouse model of asthma with AhR conditional knock out mice in AT2 cells (Sftpc-Cre;AhRf/f). The effect of AhR on allergen-induced autophagy was examined by both in vivo and in vitro analyses. The involvement of autophagy in airway inflammation was analyzed by using autophagy inhibitor chloroquine. The AhR-regulated gene profiling in AT2 cells was also investigated by RNA-seq analysis. Results: Sftpc-Cre;AhRf/f mice showed exacerbation of allergen-induced airway hyperresponsiveness and airway inflammation with elevated Th2 and airway epithelial-derived cytokines in bronchoalveolar lavage fluid (BALF). Notably, an increased allergen-induced autophagy was observed in the lung tissues of Sftpc-Cre;AhRf/f mice when compared to wild-type mice. Further analyses suggested a functional axis of AhR-TGF-β1 that is critical in driving allergic airway inflammation through regulating allergen-induced cellular autophagy. Furthermore, inhibition of autophagy with autophagy inhibitor chloroquine significantly suppressed cockroach allergen-induced allergic airway inflammation, with decreased Th2 and epithelial cell-derived cytokines in BALFs, and expression of autophagy-related genes LC3 and Atg5 in the lung tissues. Additionally, RNA-seq analysis suggests that autophagy is one of the major pathways and CALCOCO2/NDP52 and S1009 are major autophagy-associated genes in AT2 cells that that may contribute to the AhR-mediated cockroach allergen-induced allergic airway inflammation and subsequently allergic asthma. Conclusion: These results suggest that AhR in AT2 cells functions as a protective mechanism against allergic airway inflammation through controlling cell autophagy.